Bilateral Severely Stenotic Jugular Foramen: Diagnosis and Management from the Otologist/Neurotologist Point of View. (5th June 2020) - Bento, Raquel Acinho; Rodrigues, David; Levy, João; Eça, Tiago; Oliveira, Vitor; Luís, Leonel
Abstract : Bilateral jugular foramen stenosis with jugular bulb and vein aplasia is rare in nonsyndromic craniosynostosis and usually diagnosed during childhood. We present a case of bilateral jugular foramen stenosis with jugular bulb and vein aplasia, with subsequent persistence and enlargement of the fetal venous anastomosis in the middle and posterior cranial fossa, along with a review of the literature about this anatomical abnormality, highlighting the surgical challenges and management from the otologist/neurotologist point of view.